Preparing for future crises: lessons from the COVID-19 pandemic - Tan, Ming Hui (2022)
The COVID-19 pandemic has changed modern lives on an unprecedented scale and severity, teaching us lessons in terms of national policy-making and multilateral cooperation. Drawing from the experiences of Singapore and ASEAN (Association of Southeast Asian Nations) may help us better prepare for future crises.